2017
DOI: 10.3892/ol.2017.6139
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto disease in the regional lymph nodes with node metastasis in a patient with tongue cancer: A case report and literature review

Abstract: Kikuchi-Fujimoto disease (KFD), also known as histiocytic necrotizing lymphadenitis, is a rare self-limiting disorder typically affecting the cervical lymph nodes (LNs), which is often misdiagnosed as other LN-associated diseases. KFD frequently presents with necrotic lesions and recurrences, which are also features of metastatic LNs. Clinicians may thus suspect LN metastasis when they encounter ipsilateral cervical lymphadenopathy in a patient with head and neck cancer. The present study reports the case of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…At present, 10 cases of HNL combined with other tumors have been reported (Table 1 ), most of which occurred in women (7/11), predominantly in Asia (6/11), aged 27–66 years. The tumors combined with HNL were PTC [ 6 , 11 ] (2 cases), gastric carcinoma [ 12 ] (1 case), breast carcinoma [ 13 ] (1 case), squamous cell carcinoma of the tongue [ 14 ] (1 case), malignant melanoma [ 15 ] (1 case), malignant fibrous histiocytoma [ 16 ] (1 case), multiple myeloma [ 17 ] (1 case), and diffuse large B lymphoma in remission [ 18 ] (2 cases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, 10 cases of HNL combined with other tumors have been reported (Table 1 ), most of which occurred in women (7/11), predominantly in Asia (6/11), aged 27–66 years. The tumors combined with HNL were PTC [ 6 , 11 ] (2 cases), gastric carcinoma [ 12 ] (1 case), breast carcinoma [ 13 ] (1 case), squamous cell carcinoma of the tongue [ 14 ] (1 case), malignant melanoma [ 15 ] (1 case), malignant fibrous histiocytoma [ 16 ] (1 case), multiple myeloma [ 17 ] (1 case), and diffuse large B lymphoma in remission [ 18 ] (2 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Review the literature on the coexistence of HNL with other tumors: PTC [ 6 , 11 ], gastric carcinoma [ 12 ], breast carcinoma [ 13 ], squamous cell carcinoma of the tongue [ 14 ], and malignant melanoma [ 15 ], all of which occurred on the same side of the tumor as the present case, may indicate that HNL can be induced by tumor-associated local antigens and raise the possibility of specific immune responses to antigenic stimulation in HNL. Dequante et al reported a possible correlation between increased cytotoxic activity of T cells stimulated by the tumor and disease transformation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infectious background is the most suggested one, with various viral, bacterial, and parasitic pathogens suspected as causative agents for KFD [12]. There are also reports of KFD induction after breast implants [21] and with association with solid tumors [22]. SARS-CoV-2 virus may be another potential trigger of KFD.…”
Section: Discussionmentioning
confidence: 99%
“…KFD mimicking lymph node metastasis in patients with prior thyroid cancer has likewise only been reported in a few cases [20][21][22]. But differential diagnosis of the lymph node metastasis versus KFD is still limited when examined by neck ultrasound, CT scan or pos-itron emission tomography (PET) scan [23]. Since the sensitivity and specificity of neck ultrasound to detect lymph node metastasis is not good enough, LN-FNA-Tg combined with lymph node aspirate cytology may offer an accurate way to distinguish lymph node metastasis from differentiated thyroid cancers [13,14].…”
Section: Discussionmentioning
confidence: 99%